2014
DOI: 10.1371/journal.pone.0093350
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Consumer Differences in Liking during Repeated Exposure to Food; Typical Dynamics in Rating Behavior

Abstract: Consumers show high interindividual variability in food liking during repeated exposure. To investigate consumer liking during repeated exposure, data is often interpreted on a product level by averaging results over all consumers. However, a single product may elicit inconsistent behaviors in consumers; averaging will mix and hide possible subgroups of consumer behaviors, leading to a misinterpretation of the results. To deal with the variability in consumer liking, we propose to use clustering on data from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We identified three distinct patterns of consumption namely low-to-medium, high and high variability. These findings are similar to what has been reported by other studies [ 27 ] suggesting that when it comes to learning to like new foods through repeated exposure, one size does not fit all and individual differences may exist in the way children respond to familiarization [ 43 ]. Additional strategies may thus need to be implemented to increase consumption in certain groups of children who respond differently to novel foods and experiences.…”
Section: Discussionsupporting
confidence: 91%
“…We identified three distinct patterns of consumption namely low-to-medium, high and high variability. These findings are similar to what has been reported by other studies [ 27 ] suggesting that when it comes to learning to like new foods through repeated exposure, one size does not fit all and individual differences may exist in the way children respond to familiarization [ 43 ]. Additional strategies may thus need to be implemented to increase consumption in certain groups of children who respond differently to novel foods and experiences.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to availability, whether options are available (or absent) within a given environment inevitably shapes and constrains people's possible responses. The more product options that are available, the more likely it is that an actor will encounter an option they are willing to select or consume (Chernev 2011), particularly given the 'mere-exposure' effect, whereby simple repeated exposure to a product can elicit increased liking (Dalenberg 2014). Therefore, increasing the range of options for a given product or category should increase its selection or consumption -although this is of course subject to people engaging with the product in the first place, which will be influenced by many factors, including characteristics of the person (such as hunger) and of the product (such as its attractiveness or palatability).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Participants were instructed not to eat or drink during a two-hour period prior to the fMRI session, which was scheduled between 8:00 and 12:00 am or between 4:00 and 7:00 pm. Results from the remainder of the study have been reported elsewhere (see e.g., [ 21 ] )…”
Section: Methodsmentioning
confidence: 99%